Vivências de docentes e de seus licenciandos no final de formação e passagem para o mundo do trabalho : mal/bem-estar docente/discente, autoimagem e autoestima - Sampaio, Adelar Aparecido (2014)
Several studies have shown the relevance of the research aspects of the training steps in Bachelor and the transition to teaching in the early stage, given the importance of these two periods of formation are about the process of becoming a teacher, in a context of many adversities, tensions and learning that directly affect the process of teacher s development. The objective of this study focuses on the research of the personal and professional aspects of the physical education teachers to the world of work life, the first year of teaching professional and personal process, analyzing data and reports on aspects of teacher s malaise/wellness, self-image and self-esteem, experienced in these two moments of their formation. The methodology is characterized as longitudinal exploratory-descriptive study, with a qualitative approach, developed in two stages: first, in 2012, 68 undergraduates from the last half of their studies in a private institution in the State of Paraná and their teachers participated; in 2013, followed by monitoring five of them, in their transition to work life, in its first year, when we developed the continuation of the research. In the quantitative data collection instruments were used: Initial Motivation Questionnaire, Questionnaire Self Concept and Self-Esteem Questionnaire and the DASS-21, worked with descriptive and inferential statistics, using SPSS version 18; and qualitative tools: Questionnaire on Training Degree and Interviews, which were worked with content analysis of Bardin. The results from the quantitative instruments indicate that the licensees have developed self-image and self-esteem more realistic/positive motivation for teaching and levels of normality in the variables of stress, anxiety and depression. In the qualitative analysis, we selected a priori four categories, which also reveal the period of training in Licensees, considerable evidence demotivation, from the experience with adversities in the school context. We remark especially the many challenges faced in difficult situations, from interactions and experiences in the educational institution and in school and the importance of early teaching development. In the evaluation of early experiences in teaching, in four a posteriori categories, presents a considerable decrease in motivation of the teachers to continue in the profession, on account of 'reality shock'. The study identified several adverse situations experienced in the educational context, which are potential generators of teacher malaise. From the results of this research we suggest the continuity of other studies that address the period of initial experiences in Teaching, to foster the continued and ongoing development, starting with some reformulations in undergraduate courses and the initial stages in teaching, continuing the various stages of the career, with actions for the development of skills, both theoretical and practical, to meet the diverse situations of teaching universe, and contributing to generate teacher malaise, in direction of teacher s wellness.